2017
DOI: 10.1111/jpr.12154
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Social Status and Culture on Delay Discounting

Abstract: People generally tend to discount future outcomes in favor of smaller but immediate gains (i.e., delay discounting). This study examines the hypothesis that culture and social status moderate this tendency, as well as the alternative hypothesis that social status and culture influence delay discounting independently of each other. American and Japanese adults were asked to choose receiving hypothetical monetary rewards either immediately or receiving rewards of different amounts with a delay of 1 year. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…However, comparisons between populations with different demographics are rare in environmental discounting research. Although there are several studies showing differences in discounting decisions across time between people from different cultures in economics (e.g., Du et al, 2002;Ishii et al, 2017;Kim et al, 2012), cultural differences in the discounting of environmental outcomes have rarely been investigated. Where they have, discounting rate differences have been found.…”
Section: Discussionmentioning
confidence: 99%
“…However, comparisons between populations with different demographics are rare in environmental discounting research. Although there are several studies showing differences in discounting decisions across time between people from different cultures in economics (e.g., Du et al, 2002;Ishii et al, 2017;Kim et al, 2012), cultural differences in the discounting of environmental outcomes have rarely been investigated. Where they have, discounting rate differences have been found.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we screened for a range of the theoretically implicated covariates discussed above (i.e., time perspective, current affect, self-reported mental and physical health, subjective cognition, and numeracy). We also controlled for demographic characteristics since better education, higher income, and being a member of the majority racial group have been linked to reduced temporal discounting rates (e.g., Huffman et al, 2017;Ishii, Eisen, & Hitokoto, 2017). Finally, we controlled for big-five personality traits since both high neuroticism and low conscientiousness were found to be associated with a tendency to discount the future (Manning et al, 2014).…”
Section: The Present Studymentioning
confidence: 99%
“…Research has shown that a person's position in the social hierarchy is associated with perceptions of personal control (Ellis et al, 2009;Farah, 2017;Ishii et al, 2017;Sheehy-Skeffington and Rea, 2017). Regarding health behaviours, lower levels of personal control, in terms of both outcome and efficacy expectations, have been associated with performing less healthpromoting behaviours and more health-threatening behaviours (Luszczynska and Schwarzer, 2005).…”
Section: Introductionmentioning
confidence: 99%